Differential Difference Current Conveyor Transconductance Amplifier: A New Analog Building Block for Signal Processing - Neeta Pandey; Sajal K. Paul (Journal of Electrical and Computer Engineering)
A new active building block for analog signal processing, namely, differential difference current conveyor transconductance amplifier (DDCCTA), is presented, and performance is checked through PSPICE simulations which show the usability of the proposed element is up to 201 MHz. The proposed block is implemented using 0.25 μm TSMC CMOS technology. Some of the applications are presented using the proposed DDCCTA, namely, a voltage mode multifunction filter, a current mode universal filter, an oscillator, current and voltage amplifiers, and grounded inductor simulator. The feasibility of DDCCTA and its applications is confirmed via PSPICE simulations.